Accurate Second Harmonic Generation Microimprinting in Glassy Oxide Materials. Issue 6 (2nd March 2016) - Dussauze, Marc; Rodriguez, Vincent; Adamietz, Frédéric; Yang, Guang; Bondu, Flavie; Lepicard, Antoine; Chafer, Mathieu; Cardinal, Thierry; Fargin, Evelyne
Abstract : Spatial and geometry controls of second order optical properties at the micrometer scale have been achieved on borophosphate niobium glasses by thermal poling using micropatterned anode electrodes. Electrode structuring should induce local field enhancement, which is observed at the edges of an indium tin oxide‐ablated layer. A lateral poling effect governs the geometry and the strength of the electric field implemented. The potential of such process to fabricate large scale microstructured periodical design of second order optical properties has been demonstrated. Abstract : Spatial and geometry controls of second order optical properties in glassy materials can be achieved at the micrometer scale by an imprinting poling process. This accurate second harmonic generation (SHG) imprinting procedure allows fabricating a microstructured periodical design of second order optical properties on very large scales.